2009
DOI: 10.1021/ja902951b
|View full text |Cite
|
Sign up to set email alerts
|

Colorimetric Split G-Quadruplex Probes for Nucleic Acid Sensing: Improving Reconstituted DNAzyme’s Catalytic Efficiency via Probe Remodeling

Abstract: Split G-rich DNA probes can assemble into active peroxidase-mimicking DNAzymes in the presence of bioanalytes such as DNA, thereby providing a simple and cheap means to detect analytes in biological samples. A comprehensive study designed to reveal the salient probe architectural features and reaction conditions that facilitate facile reconstitution into enzymatically proficient enzymes unveiled these important findings: (a) The loops that connect the G3-tracts in a G-quadruplex structure can be replaced with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
170
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 197 publications
(174 citation statements)
references
References 63 publications
3
170
0
1
Order By: Relevance
“…Also, it remains to be shown if the peroxidation of organic molecules by G-quadruplexes takes place in a special binding pocket or site. Others have proposed that G-quadruplexes with anti-parallel topology are the active peroxidation catalysts [19,20] whereas our group [15,16] and others [12,14,21] have shown that G-quadruplexes with parallel or mixed-hybrid topologies are catalytically more proficient than anti-parallel G-quadruplexes. In this paper, we reveal that oligonucleotides that have a high propensity to form anti-parallel G-quadruplexes but are not peroxidase enzymes can indeed be turned into active peroxidation catalysts through the covalent attachment of hemin co-factor.…”
Section: Introductionmentioning
confidence: 70%
See 4 more Smart Citations
“…Also, it remains to be shown if the peroxidation of organic molecules by G-quadruplexes takes place in a special binding pocket or site. Others have proposed that G-quadruplexes with anti-parallel topology are the active peroxidation catalysts [19,20] whereas our group [15,16] and others [12,14,21] have shown that G-quadruplexes with parallel or mixed-hybrid topologies are catalytically more proficient than anti-parallel G-quadruplexes. In this paper, we reveal that oligonucleotides that have a high propensity to form anti-parallel G-quadruplexes but are not peroxidase enzymes can indeed be turned into active peroxidation catalysts through the covalent attachment of hemin co-factor.…”
Section: Introductionmentioning
confidence: 70%
“…We [15] and others [23] have shown that oligonucleotide G1 [24] (5'-(G) 3 TA(G) 3 C(G) 3 TT(G) 3 T-3') mainly exists as a parallel or a mixed-hybrid conformer in the presence of monovalent cations (such as Na + , K + , or NH 4 + ). G1 binds to hemin and this is manifested spectroscopically as an increase in intensity as well as a slight red shift (398 to 404 nm) in the Soret band of hemin when increasing concentrations of G1 are added to hemin (see Figure 2 A).…”
Section: Resultsmentioning
confidence: 93%
See 3 more Smart Citations